External stress as a way to control Au(111) reconstruction - Chauraud, Dimitri; Durinck, J.; Vernisse, L.; Smalley, S.; Drouet, M.; Coupeau, C. (Surface Science, 2021)
We report investigations on gold single crystals carried out with the help of an original experimental set-up, combining a scanning tunneling microscope and a compression device under ultra high vacuum, that allows for in situ observations of stressed surfaces at the atomic scale. It is observed that a macroscopic compression strain may induce a reorganization of the Au(111) surface reconstruction, known as the chevron-like pattern. Molecular dynamics simulations using a modified embedded atom method potential have been carried out to highlight the elementary dislocation mechanisms at the origin of such an evolution.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Molecular Dynamics; Scanning Tunneling Microscopy; Surface Reconstruction

Laves phase crystal analysis (LaCA): Atomistic identification of lattice defects in C14 and C15 topologically close-packed phases - Xie, Zhuocheng; Chauraud, Dimitri; Bitzek, Erik; Korte-Kerzel, Sandra; Guénolé, Julien (Journal of Materials Research, 2021)
Abstract: The identification of defects in crystal structures is crucial for the analysis of atomistic simulations. Many methods to characterize defects that are based on the classification of local atomic arrangement are available for simple crystalline structures. However, there is currently no method to identify both, the crystal structures and internal defects of topologically close-packed (TCP) phases such as Laves phases. We propose a new method, Laves phase crystal analysis (LaCA), to characterize the atomic arrangement in Laves crystals by interweaving existing structural analysis algorithms. The new method can identify the polytypes C14 and C15 of Laves phases, typical crystallographic defects in these phases, and common deformation mechanisms such as synchroshear and non-basal dislocations. Defects in the C36 Laves phase are detectable through deviations from the periodic arrangement of the C14 and C15 structures that make up this phase. LaCA is robust and extendable to other TCP phases. Graphic abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-05-28